Formulation Of Fire Safety Evacuation Management Strategy For The Government Hospital Buildings - Sadek Bacha, Muhammad Amin (2022)
The purpose of this research is not only to investigate fire safety evacuation management, but also to redefine the fulfilment of the design criteria of needed Means of Escape (MOE) by-Laws and other associated fire safety rules and regulations and to assess the building's compliance with the evacuation code. The study also seeks to develop parameters for fire safety management at the Government hospital buildings. This research has been essential in raising the issue on the need for efficient and effective fire safety measures in public spaces especially hospitals to promote the safety of the general public.